Polycythaemia Rubra Vera With Incisional Hernia Surgery- A Very Rare Case Report (Journal of Dhaka Medical College, 2020)
Polycythaemia rubra vera is a chronic myeloproliferative disorder that is characterized by excessive red cell production and unlike other forms of polycythaemia, it can cause both bleeding and thrombosis in the same patient. Only few cases have been reported in the literature where polycythaemia rubra vera with surgery was performed successfully .The ideal peri-operative management is currently unknown. Here we present a case of 50 yrs old lady with polycythaemia rubra vera underwent open mesh repair for incisional hernia. After operation, the patient developed hemorrhagic complications needing resuscitation with blood and plasma expander. The patient was managed efficiently. Considering its very rarity, we are reporting the case.J Dhaka Medical College, Vol. 27, No.2, October, 2018, Page 218-222